EXPLORING CONNECTIVITY AND TRAVERSABILITY IN GRAPHS: A COMPREHENSIVE STUDY (International Journal of Food and Nutritional Sciences, 2022)
The aim of this paper is to explore the Connectivity and Traversability in Graphs. Graphs are essential mathematical structures used to represent and analyze relationships between pairs of entities. They are comprised of vertices (nodes) connected by edges, which can be either directed or undirected. The study of connectivity and traversability within graphs is fundamental for understanding and solving various problems in network design, optimization, and data analysis. Connectivity in graphs refers to the degree to which vertices are interconnected. It includes vertex connectivity, the minimum number of vertices needed to disconnect the graph, and edge connectivity, the minimum number of edges required for disconnection. These metrics are crucial for assessing the robustness and resilience of networks. In undirected graphs, connectivity is characterized by the presence of paths between all pairs of vertices, while in directed graphs, connectivity encompasses strong and weak connectivity, reflecting the directionality of edges.